Creative Writing Using Scaffolding of Vladimir Propp Theory-Based - Basuki, Edi Pujo; Djuwari, Djuwari; Saputri, Tiyas; Authar, Nailul; Afandi, Mujad Didien (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to prove whether students’ writing creativity can be increased by implementing the plot of the Black Adam movie based on Propp’s morphology structure as scaffolding in making a narrative story. This study was conducted because students feel the necessity and lack self-motivation to create their own story. Methods – This research was quantitative with an experimental design. The data collected from the pre-test and post-test results were then analyzed by quantitative analysis through SPSS 25. The sample for this research was 25 students of English education in the first Semester, at the University of Nahdlatul Ulama Surabaya. There were two kinds of instruments for this data, such as tests (pre-test and post-test) and questionnaires. The questionnaire was collected by diagram through a Google form.Findings – The result of this study showed students’ writing creativity increased by using the Vladimir Propp structure in making fairy tale stories, with p = 0.00 > 0.05. This suggests that the implementation of the Black Adam movie’s plot in creative writing based on Propp’s Morphology of Fairytale improved students’ writing ability in making narratives and helped students learn more easily. Research Implications – This research is limited by a small sample, a short duration, and a single-group design. Generalizing findings is challenging, and future research should consider larger and more diverse samples, extended study durations, and diverse pedagogical approaches for a comprehensive understanding of effective creative writing instruction.